PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA PADA MATERI TATA SURYA IPAS KELAS 6 SDN KARANGNANGKA II - Masrur, Moh.; Ahmad Siddiq; Ike Yuli Mestika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Discovery Learning learning model based on Augmented Reality on student learning outcomes in the solar system material in grade VI of SDN Karangnangka II. This learning model allows students to actively explore concepts independently, while Augmented Reality (AR) technology provides a more interactive and visual learning experience. The research method used is quantitative with a Pre-experimental experimental design of the One Group Pretest-Posttest Design type. The research sample consisted of 10 grade VI students selected using a saturated sample technique. Data were collected through written tests in the form of pre-tests and post-tests, then analyzed using parametric statistical tests with the help of SPSS 25. The results showed a significant increase in student learning outcomes after the application of the Discovery Learning model based on Augmented Reality, which can be seen from the difference in average pre-test scores (46.70) and post-test (57.30). The paired samples test statistical test showed a significance value of 0.000 (<0.05), which indicates that this learning model contributes significantly to improving student learning outcomes. Thus, the Augmented Reality-based Discovery Learning model can be used as an innovative alternative to increase the effectiveness of science learning, especially on solar system material.